Peran Digital dalam Membentuk Pola Interaksi Komunikasi Interpersonal Generasi Z - Muhamad Syarif Hidayatullah; Rini Rusnawati; Gita Belaroza; Bunga Astri Cahya Nabiyina; April Laksana (STIKes Ibnu Sina Ajibarang, 2025)
Generasi Z, a younger generation in the digital era, uses active social media for effective communication. They use emojis and group chats, but are less formal in formal communication and more informal. Digital communication has both positive and negative effects on their social interactions. Education on media literacy and information literacy is crucial for Genrasi Z to improve critical thinking and interpersonal communication skills.